2014
DOI: 10.3389/fonc.2014.00118
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of β-Catenin, E-Cadherin, and SOX9 in Colorectal Cancer: Results from a Large Population-Representative Series

Abstract: Robust biomarkers that can precisely stratify patients according to treatment needs are in great demand. The literature is inconclusive for most reported prognostic markers for colorectal cancer (CRC). Hence, adequately reported studies in large representative series are necessary to determine their clinical potential. We investigated the prognostic value of three Wnt signaling-associated proteins, β-catenin, E-cadherin, and SOX9, in a population-representative single-hospital series of 1290 Norwegian CRC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 69 publications
7
62
1
1
Order By: Relevance
“…SOX9 has been reported to be highly expressed in a number of types of human cancer, such as prostate (36), breast (37) and colorectal (38) cancer. In NSCLC, SOX9 was upregulated at mRNA and protein levels, and the expression levels were associated with the histological stage of NSCLC and patients with a high SOX9 level exhibited a shorter survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 has been reported to be highly expressed in a number of types of human cancer, such as prostate (36), breast (37) and colorectal (38) cancer. In NSCLC, SOX9 was upregulated at mRNA and protein levels, and the expression levels were associated with the histological stage of NSCLC and patients with a high SOX9 level exhibited a shorter survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Study cohort 1 is a population‐representative consecutive series of CRC patients from Oslo University Hospital Aker, and has been previously reported 16, 17, 18. Briefly, all patients with CRC from 1993 to 2003 were registered and clinical data were prospectively recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, all patients with CRC from 1993 to 2003 were registered and clinical data were prospectively recorded. Of the 1290 patients included, 929 underwent a major resection and had tumor samples available for tissue microarray (TMA) construction 17. Colon cancer patients ≤75 years of age and all rectal cancer patients who underwent curative surgery entered a 5‐year follow‐up program as described previously 18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voorham et al (120) reported observation of methylated Wnt pathway antagonists from clinical specimens. It is possible that the Wnt signaling pathway could also be used as a potential diagnostic and prognostic biomarker in CRC patients (119,121). Thus, both experimental and clinical data showed that the over activation of the Wnt signaling pathway may be a potential target for CRC.…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%